Our first experience with primary lip repair in newborns with cleft lip and palate - Borský, J; Tvrdek, M; Kozák, J; Cerný, M; Zach, J (Acta chirurgiae plasticae, 2007)
The article summarizes the results of early primary lip repair in 44 newborns with cleft lip and palate. We present a study of the first 44 patients to undergo the surgery before the age of 1 week as performed by a surgeon who used a modified method according to Tennison with a nasal correction. Early lip surgeries started in 2005. Cleft patients are under the care of a multidisciplinary team. Preliminary results are very encouraging; we observed excellent esthetic results concerning lip scars and the appearance of the nose. We did not notice any impact on the maxillary development due to the short time interval. We consider early lip surgery with nasal correction the best method, and we would like to continue with it, monitoring its impact on the maxillary and nasal development.
Keywords: Cleft Palate; Rhinoplasty; novorozenec; Infant, Newborn; rozštěp patra; rozštěp rtu; Cleft Lip; Humans; Infant; zákroky plastické chirurgie; lidé; rinoplastika; kojenec; Plastic Surgery Procedures